Bosonic D-branes at finite temperature - Vancea, I. V. [UNESP] (Elsevier, 2000)
We derive the finite temperature description of bosonic D-branes in the thermo field approach. The results might be relevant to the study of thermical properties of D-brane systems. (C) 2000 Published by Elsevier Science B.V.